The refurbishment of top lighting and its impact on the visual environment in the industrial hall : a case study (2019)
Natural daylight is a vital element in our daily life. Providing natural daylight into the working environment is of fundamental importance for the comfort, efficiency and safety for the people in that environment. This paper deals with visual comfort evaluation in selected hall. The aim of this study was to evaluate existing and reconstructed industrial hall lighting by measuring daylight. The measurement was carried out in the hall with two types of skylights and with the refurbishment of the side lighting.